2021
DOI: 10.3389/fcell.2021.652972
|View full text |Cite
|
Sign up to set email alerts
|

OGP46 Induces Differentiation of Acute Myeloid Leukemia Cells via Different Optimal Signaling Pathways

Abstract: Acute myelogenous leukemia (AML) is characterized by blockage of cell differentiation leading to the accumulation of immature cells, which is the most prevalent form of acute leukemia in adults. It is well known that all-trans retinoic acid (ATRA) and arsenic trioxide (ATO) are the preferred drugs for acute promyelocytic leukemia (APL). However, they can lead to irreversible resistance which may be responsible for clinical failure after complete remission (CR). Moreover, the differentiation therapy of ATRA-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…As a classic differentiation-inducing drug, ATRA has transformed APL from being highly fatal to being highly curable, and the ATRA/arsenic combination programme has cured almost all patients with standard risk APL. 29,30 Interestingly, the effect of ATRAinduced differentiation is insufficient for APL eradication, whereas only PML/RARA loss fully extinguish leukaemia-initiating activity. 31 Therefore, ATRA/arsenic combination programme exerts an anti-tumour effect by induced PML/RARA degradation in cells, from which anti-tumour efficacy could be dissociated from the trancriptomic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a classic differentiation-inducing drug, ATRA has transformed APL from being highly fatal to being highly curable, and the ATRA/arsenic combination programme has cured almost all patients with standard risk APL. 29,30 Interestingly, the effect of ATRAinduced differentiation is insufficient for APL eradication, whereas only PML/RARA loss fully extinguish leukaemia-initiating activity. 31 Therefore, ATRA/arsenic combination programme exerts an anti-tumour effect by induced PML/RARA degradation in cells, from which anti-tumour efficacy could be dissociated from the trancriptomic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, differentiation therapy is a novel treatment for AML. As a classic differentiation‐inducing drug, ATRA has transformed APL from being highly fatal to being highly curable, and the ATRA/arsenic combination programme has cured almost all patients with standard risk APL 29,30 . Interestingly, the effect of ATRA‐induced differentiation is insufficient for APL eradication, whereas only PML/RARA loss fully extinguish leukaemia‐initiating activity 31 …”
Section: Discussionmentioning
confidence: 99%
“…Kasumi-1 was incubated with 0.5 μM of I13 for 48 h, and the cells were collected for RNA extraction and mRNA sequencing analysis. As described in our previous work ( 16 , 17 ), the cDNA library was sequenced by Illumina genome analyzer. Levels of gene expression were estimated using fragments per kilobase of exon per million fragments mapped (FPKM) values.…”
Section: Methodsmentioning
confidence: 99%
“…The chemical structure of JOA and its analog OGP46 ( Zhao et al, 2021 ) is shown in Figure 1A . The molecular weight of JOA is 348.2.…”
Section: Methodsmentioning
confidence: 99%